PERANCANGAN MEDIA PEMBELAJARAN INTERAKTIF MATERI SEMESTER 2 STUDI KASUS DI TK WAHYU HIDAYAH DESA PAGERSARI KABUPATEN SEMARANG - Firdaus Aditya; Daniel Rudjiono; Bambang Suhartono (STEKOM PRESS, 2019)
The goal to be achieved in research is to make it interactive 2nd semester learning material for Wahyu Hidayah Kindergarten, Pagersari Village. This matter against the background by the medium of learning masish using paper that lacking evision. The purpose of this making use Adobe Flash CS 5 media is to be able to provide convenience in the delivery of learning Interactive multimedia is a media that consists of manyncomponents or media that are connected to one another and are able to interact. Teaching media in the form of interactive multimedia has the ability to save audio visual data, make multimedia especially interactive learning as a supporter of the learning method that was once conveyed through books and direct explanations that are not easily digested by children, so expect the use of interactive CD media that aims to improve learning outcomes can explain that learning media interactive able to provide more interesting and interesting information a lot of fun In collecting data, the method used by the author is by using observation and survey methods. For the making using the Adobe Auditions CS5, Adobe Photoshop CS5, Adobe programs Flash CS5, CorelDraw X5, Format Factory, is expected in the presence of media interactive learning can increase children's interest in learning.